(untitled) (World Bulletin of Education and Learning, 2025)
This study explores the transformation of pedagogical skills and the emergence of innovative teaching approaches within the context of digital education in pedagogical universities. The rapid integration of digital technologies into educational systems has significantly reshaped the professional role of teachers, requiring not only subject-matter expertise but also advanced digital, methodological, and reflective competencies. The research focuses on how pedagogical skills evolve under digital conditions and how innovative approaches contribute to improving the quality and effectiveness of the teaching and learning process. Special attention is given to the alignment between traditional pedagogical mastery and modern digital tools, platforms, and instructional strategies. The study analyzes the conceptual foundations of pedagogical skills in a digital environment, emphasizing adaptability, creativity, communication, and learner-centeredness as key professional attributes. Innovative approaches such as blended learning, project-based learning, flipped classrooms, and digital collaboration are examined as mechanisms that enhance instructional flexibility and student engagement. The research highlights the role of teachers as facilitators, designers of digital learning environments, and mentors who guide students in developing critical thinking and self-directed learning skills. Based on theoretical analysis and empirical observations, the study identifies key challenges faced by teachers, including digital readiness, pedagogical integration of technology, and the need for continuous professional development. The